Factors associated with self-reported diabetes according to the 2013 National Health Survey - Malta, Deborah Carvalho; Bernal, Regina Tomie Ivata; Iser, Betine Pinto Moehlecke; Szwarcwald, Célia Landmann; Duncan, Bruce Bartholow; Schmidt, Maria Inês (Revista de Saúde Pública, 2017)
OBJECTIVES To analyze the factors associated with self-reported diabetes among adult participants of the National Health Survey (PNS). METHODS Cross-sectional study using data of the PNS carried out in 2013, from interviews with adults (≥ 18 years) of 64,348 Brazilian households. The prevalence of self-reported diabetes, assessed by the question “Has a doctor ever told you that you have diabetes?,” was related to sociodemographic characteristics, lifestyle, self-reported chronic disease, and self-evaluation of the health condition. Prevalence ratios were adjusted according to age, sex, and schooling by Poisson regression with robust variance. RESULTS The diagnosis of diabetes was reported by 6.2% of respondents. Its crude prevalence was higher in women (7.0% vs. 5.4%), and among older adults, reaching 19.8% in the elderly. Black adults who received less schooling showed higher prevalence. Among those classified as obese, 11.8% reported having diabetes. Ex-smokers, those insufficiently active and those who consume alcohol abusively reported diabetes more often. Differences were not verified in eating habits among adults who reported, or did not, diabetes. A relation between diabetes and hypertension was found. CONCLUSIONS After adjustment according to age, schooling and sex, diabetes was shown to be associated with higher age, lower schooling, past smoking, overweight and obesity, and hypertension, as well as with a self-declared poor state of health, indicating a pattern of risk factors common to many chronic non-communicable diseases and the association of the disease with morbidity.